Antimicrobial Susceptibility Trends of Streptococcus pneumoniae by Age Groups Over Recent 10 Years in a Single Hospital in South Korea - Oh, Hyunjoo; Heo, Sang Taek; Kim, Misun; Kim, Young Ree; Yoo, Jeong Rae (Yonsei medical journal, 2021)
( ) causes respiratory tract infections. Its non-vaccine serotypes and multidrug-resistant pneumococcal diseases have increased during the post-pneumococcal vaccination era. Therefore, it is important to understand the regional and age-related antimicrobial susceptibility of to select appropriate empirical antimicrobials. We retrospectively studied trends in the antimicrobial resistance of to commonly prescribed antibiotics in patient groups of various ages at a single teaching hospital in Jeju Island from 2009 to 2018. In total, 1460 isolates were obtained during the study period. The overall antimicrobial resistance rates of to penicillin, erythromycin, ceftriaxone, levofloxacin, and vancomycin were 16.2%, 84.7%, 25.9%, 3.3%, and 0.0%, respectively, and the MDR rate was 6.7%. Erythromycin and ceftriaxone resistance rates increased by years; however, they were significantly reduced in adult groups. Levofloxacin resistance and MDR rates were also higher in adult groups. Overall, the MDR rate significantly increased during the recent 10 years, as well as in patients with a history of hospitalization within 90 days [odds ratio (OR)=3.58, 95% confidence interval (CI)=1.91-6.71] and sinusitis (OR=4.98, 95% CI=2.07-11.96). Erythromycin and ceftriaxone resistance rates and the MDR rate of significantly increased during the recent 10 years; the trends in individual antimicrobial resistance rates significantly differed between the age groups. This study indicates the need for caution when using ceftriaxone as an empirical antimicrobial against pneumococcal infections.